Antibiotic susceptibility of staphylococcus epidermidis among undergraduate students in Malaysia public university health campus - Abu Mansor, Abu Zarrin; Mohd Amin, Nor Munirah; Enche Othman, Mohamad Izwan; Ahmad Suaidan, Abdullah; Ahmad Yusof @ Hanafi, Hanani (Penerbit Universiti Kebangsaan Malaysia, 2020)
Staphylococcus epidermidis (S. epidermidis) has become one of the major concerns in the hospital setting due to its ability to cause hospital-acquired infection particularly from medical device contamination. The management of S. epidermidis infections become more challenging with the increase of antimicrobial resistance cases over the past years. Limited reports on S. epidermidis antibiotic resistance among healthy people leave uncertainty about the magnitude of antimicrobial resistance spreads among the community. Therefore, this study aimed to identify the antibiotic susceptibility pattern of S. epidermidis isolated from healthy undergraduate students in one of Malaysia public universities health campuses. Ninety-six hand palm swab samples were collected and undergo several tests, including microscopic, biochemical identification tests and antibiotic susceptibility test for erythromycin, oxacillin, gentamicin, penicillin and tetracycline following Kirby-Bauer test. A total of 43 samples showed the presence of S. epidermidis (44.8%), where 72.1% of the isolates showed resistance towards at least one type of antibiotic. The highest and lowest resistance was observed for penicillin and gentamycin, respectively. Although there is no significant difference of antibiotic susceptibility pattern was observed between genders, the presence of high antibiotic resistance in S. epidermidis among these healthy communities should warrant further investigation since the spreading of the resistant strain could occur in the wider community population without notice. ******************************************************************************* Staphylococcus epidermidis (S. epidermidis) menjadi salah satu keprihatinan utama dalam pengurusan hospital berikutan kebolehannya menyebabkan jangkitan perolehan hospital terutamanya daripada alatan perubatan yang tercemar. Pengurusan jangkitan S. epidermidis semakin mencabar dengan peningkatan kes kerintangan terhadap antibiotik sejak kebelakangan ini. Laporan terhad mengenai kerintangan terhadap antibiotik oleh S. epidermidis di kalangan kumpulan komuniti yang sihat meninggalkan satu persoalan mengenai tahap penyebaran bakteria rintang antibiotik di kalangan komuniti. Oleh itu, kajian ini bertujuan untuk mengenalpasti corak rentan antibiotik oleh S. epidermidis yang dipencilkan daripada pelajar-pelajar sihat di salah satu kampus kesihatan di universiti awam. Sebanyak 96 sampel sapuan telapak tangan telah diambil dan melalui beberapa ujikaji termasuk ujian pengenalpastian secara mikroskopik, biokimia dan juga ujian rentan antiobiotik untuk eryhtromycin, oxacillin, gentamicin, penicillin dan tetracycline menerusi ujian Kirby Bauer. Sejumlah 43 sampel menunjukkan kehadiran S. epidermidis (44.8%), di mana 72.1% daripada jumlah pencilan bakteria ini menunjukkan kerintangan terhadap sekurang-kurangnya satu jenis antibiotik. Tahap kerintangan tertinggi dan terendah masing-masing didapati pada penicillin dan gentamicin. Walaupun tiada perbezaan yang signifikan antara corak rentan antibiotik antara kumpulan jantina, tahap kerintangan antibiotik yang tinggi di kalangan komuniti sihat menunjukkan terdapat keperluan terhadap kajian lanjut kerana penyebaran strain bakteria rintang antibiotik boleh berlaku kepada populasi komuniti lain dengan lebih meluas dan tanpa disedari.